Development of moisture sensor interface using Arduino / Mohd Faiz Sulong @ Ismail - Sulong @ Ismail, Mohd Faiz (2012)
This project is to develop an interface sensor’s signal to the board and shows the data read from the sensor using LCD and connected to PC using a serial monitor. The data of soil’s resistivity from the sensor is transmitted to Arduino. Arduino then will convert it to volumetric water content(VWC) value and displayed it on LCD or serial data on PC . The implementation of the study used a microcontroller that was called Arduino Uno and integrated with SD card shield module as the data collector. From the testing it shows that the sensor capable to read 1% to 79% of moisture sensor based on the calibration made.